Base‐Catalyzed Intramolecular Hydroamination of Cyclohexa‐2, 5‐dienes: Insights into the Mechanism through DFT Calculations and Application to the Total Synthesis of epi‐Elwesine. Issue 45 (15th September 2014) - Rousseau, Géraldine; Lebeuf, Raphaël; Schenk, Kurt; Castet, Frédéric; Robert, Frédéric; Landais, Yannick
Abstract The base‐catalyzed intramolecular hydroamination of 1‐ethylaminocyclohexa‐2, 5‐dienes is described. The transformation proceeds through isomerization of the cyclohexa‐1, 4‐dienyl fragment into the corresponding conjugated 1, 3‐diene prior to the hydroamination step. Attaching a chiral glycinol ether auxiliary on the amino group allows the protonation to occur with complete diastereocontrol. The resulting lithium amide then adds onto the 1, 3‐dienyl moiety, affording the desired fused pyrrolidine ring along with the corresponding lithium allylic anion. Protonation of the latter then proceeds with high regiocontrol to favor the resulting allylic amines. In contrast, when the reaction was performed on primary amines, fused pyrrolidines bearing a homoallylic amino group were obtained. The stereochemical course of the process and determination of the reaction pathways were established based on calculations performed at the DFT level. Finally, application of the methodology to the enantioselective synthesis of (+)‐epi‐elwesine, a crinane alkaloid, is described.